Absent muscle coordination patterns and reduced force exertion in the novice of clean exercise - Kibushi, B.; Sado, N.i; Kouzaki, M. (ISBS Proceedings Archive (Michigan), 2020)
The clarification of the problems to perform the clean in novice obtains several suggestions for technical guidance. We aimed to identify the control of muscle coordination patterns and related kinetic problems during the clean. Five experienced participants (EXP) and five novices (NOV) performed the clean. The synchronous activation patterns among several muscles were extracted using a decomposition technique. The median number of patterns in NOV (2) was smaller than that of EXP (4). We specified the absent pattern, which was related to the activation of lower limb extensors at the termination of the scoop phase. This might lead to insufficient ankle plantarflexion torque or backward ground reaction forces for pulling the barbell. A practical implication is that a novice needs to pay attention to learning the appropriate activation timing of lower limb extensors for sufficient force exertion.